On the convergence rate of interval repeated midpoint zoro symmetric single-step procedure for simultaneous bounding the polynomial zeros - Monsi, Mansor; Mohammad Rusli, Syaida Fadhilah; Senu, Norazak; Ismail, Fudziah; Ibrahim, Zarina Bibi (AIP Publishing LLC, 2013)
In this paper, we present the analysis of the rate of convergence of the interval repeated midpoint zoro symmetric single-step procedure (IRMZSS) which is the extension of the interval midpoint zoro symmetric single-step procedure (IMZSS). The results show that the procedure IRMZSS has R-order of convergence at least 7r + 1 (r ≥ 1) or 0R (IRMZSS) ≥ 7 r + 1 (r ≥ 1), whereas the procedure IMZSS R-order of convergence at least 8 or 0R (IMZSS) ≥ 8. In fact 0R (IRMZSS) ≥ 0R (IMZSS) and 0R (IRMZSS) = 0R (IRMZSS) = 0R (IMZSS) when r = 1.